2009
DOI: 10.1002/jcb.22125
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO‐E3 ligase PIAS3 targets pyruvate kinase M2

Abstract: Pyruvate kinase M2 (M2-PK) controls the rate-limiting step at the end of the glycolytic pathway in normal proliferating and tumor cells. Other functions of M2-PK in addition to its role in glycolysis are little understood. The aim of this study was to identify new cellular interaction partners of M2-PK in order to discover novel links between M2-PK and cellular functions. Here we show that the SUMO-E3 ligase protein PIAS3 (inhibitor of activated STAT3) physically interacts with M2-PK and its isoenzyme M1-PK. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 45 publications
1
54
0
1
Order By: Relevance
“…The relative importance of these processes remains to be determined but has been shown to be essential in the glycolytic pathways of some human protozoan parasites, trypanosomes (34). Furthermore, a recent study demonstrated the interaction of SUMO-1, the SUMO E3 ligase PIAS3, and the ratelimiting glycolytic enzyme, pyruvate kinase (36). Whether this interaction of pyruvate kinase with SUMO has any effects on its enzyme activity or its interaction with other glycolytic enzymes is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of these processes remains to be determined but has been shown to be essential in the glycolytic pathways of some human protozoan parasites, trypanosomes (34). Furthermore, a recent study demonstrated the interaction of SUMO-1, the SUMO E3 ligase PIAS3, and the ratelimiting glycolytic enzyme, pyruvate kinase (36). Whether this interaction of pyruvate kinase with SUMO has any effects on its enzyme activity or its interaction with other glycolytic enzymes is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This isomerization of PKM2 exposes its nuclear localization sequence (NLS) and promotes its binding to importin a5, which facilitates its nuclear translocation (Yang et al, 2012c). In addition, sumoylation of PKM2 mediated by the SUMO-E3 ligase PIAS3, and acetylation of PKM2 at K433 mediated by the p300 acetyltransferase (also known as EP300) prevent the binding of FBP to PKM2, thereby enhancing its nuclear translocation (Lv et al, 2013;Spoden et al, 2009). …”
Section: Regulation Of the Subcellular Localization Of Pkm2mentioning
confidence: 99%
“…A variety of molecules interact with PKM2 (5,6,8,14,18,19,21,23,24,28,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Many of them affect the glycolytic functions of PKM2, which directly regulate the Warburg effect.…”
Section: Nonglycolytic Functions Of Pkm2mentioning
confidence: 99%